2020
DOI: 10.1111/os.12750
|View full text |Cite
|
Sign up to set email alerts
|

Ferric Ion Induction of Triggering Receptor Expressed in Myeloid Cells‐2 Expression and PI3K/Akt Signaling Pathway in Preosteoclast Cells to Promote Osteoclast Differentiation

Abstract: Objective Iron plays a significant role in multiple biological processes. The purpose of this study was to measure whether iron mediated osteoclast differentiation through regulation of triggering receptor expressed in myeloid cells‐2 (Trem‐2) expression and the PI3K/Akt signaling pathway. Methods The effects of six different concentrations of ferric ammonium citrate (FAC) (100, 80, 40, 20, 10 and 0 μmol/L) on RAW 264.7 cells proliferation were assessed by Cell Counting Kit‐8 (CCK‐8) gassay. Tartrate resistant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…TREM-1 induces inflammation and lipid accumulation in human hepatoma cell line HepG2 and primary mouse hepatocytes by activating the PI3K-AKT pathway 74 . TREM-2 promotes the differentiation of osteoclasts, increases the production of inflammatory factors, and enhances the killing effect of bacteria in the murine macrophage cell line RAW264.7 through the PI3K–AKT pathway 75 , 110 , 111 . sTREM-2 is dependent on the PI3K–AKT pathway to induce inflammation of microglia, promoting their survival and enhancing its phagocytic function in vivo and in vitro 73 , 105 .…”
Section: Discussionmentioning
confidence: 99%
“…TREM-1 induces inflammation and lipid accumulation in human hepatoma cell line HepG2 and primary mouse hepatocytes by activating the PI3K-AKT pathway 74 . TREM-2 promotes the differentiation of osteoclasts, increases the production of inflammatory factors, and enhances the killing effect of bacteria in the murine macrophage cell line RAW264.7 through the PI3K–AKT pathway 75 , 110 , 111 . sTREM-2 is dependent on the PI3K–AKT pathway to induce inflammation of microglia, promoting their survival and enhancing its phagocytic function in vivo and in vitro 73 , 105 .…”
Section: Discussionmentioning
confidence: 99%
“…RANKL and RANK binding activates several intracellular signaling pathways in osteoclast precursors, mainly including NF-κB and MAPKs ( Amarasekara et al, 2018 ; An et al, 2019 ; Liu et al, 2020 ). NF-κB is essential for RANKL-induced osteoclastogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Liu et al. also found that the ferric ammonium citrate could promote osteoclast differentiation through the Trem-2-mediated PI3K/AKT signaling pathway [ 39 ]. Based on the important role of this pathway in bone-related diseases, we further studied the effect of miR-4739 on the PI3K/AKT pathway in osteoblasts.…”
Section: Discussionmentioning
confidence: 99%